Folk Taxonomy of Fish in Kaera Language - Leo, Haniva Yunita (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2022)
This paper describes ethnosemantic system of fish classification in Kaera Language, a papuan language spoken in East Pantar, Alor Regency, East Nusa Tenggara, Indonesia. The aims of this study are to document vernacular names of fish in Kaera Language, to classify them using folk taxonomy proposed by Berlin (1992), and to describe the fish naming system in Kaera community. The data were collected by employing quasi-experimental method, resulting in 63 terms of fish in Kaera language. The data were then transcribed and classified based on their taxa in folk taxonomy (Berlin, 1992). The result of data analysis showed that fish in Kaera Language are classified into four levels of taxonomy hierarchy namely unique beginner, life form, generic and specific. While regarding folk nomenclature, Kaera community name the fish by their appearance, habitat, and imagination, reflecting their cultural perspective that is influenced by nature around them. AbstrakMakalah ini mendeskripsikan sistem pengklasifikasian ikan secara etnosemantik dalam bahasa Kaera, bahasa yang termasuk rumpun bahasa papua, dituturkan oleh masyarakat Pantar Timur, Kabupaten Alor, Provinsi Nusa Tenggara Timur. Tujuan penulisan makalah ini adalah untuk mendokumentasikan nama-nama ikan dalam bahasa Kaera, mengklasifikasikannya berdasarkan taksonomi daerah yang diusulkan oleh Berlin (1992), dan mendeskripsikan sistem penamaannya dalam masyarakat Kaera. Data dalam kajian ini dikumpulkan menggunakan metode kuasi-eksperimen, menghasilkan 63 istilah ikan dalam bahasa Kaera. Data yang terkumpul kemudian ditranskripsi dan diklasifikasikan berdasarkan taksa dalam taksonomi rakyat (Berlin, 1992). Hasil kajian ini menunjukkan bahwa ikan dalam bahasa Kaera diklasifikasikan ke dalam empat level hirarki taksonomi, yakni unique beginner, life form, generic, dan specific. Sementara itu, berkaitan dengan nomenklatur, masyarakat Kaera menamai ikan berdasarkan tampilan, habitat, dan imajinari, merefleksikan perspektif budaya masyarakat Kaera yang dipengaruhi oleh alam di sekitar mereka.